Nonlinear reservoir analysis with risk-benefit objectives - Otto J. Helweg (2018)
The surrogate worth trade-off method has been extended to a quadratic programming optimization model and risk has been incorporated into the vector of objective functions which explicitly shows the decision maker the trade-offs between net benefits and increased reliability of the system or the trade-offs between competing reliabilities such as flood control and water supply. The approach is called the Nonlinear Risk-Benefit (NRB) Algorithm. The NRB Algorithm is applied to the Broken Bow Reservoir to illustrate the increased information made available by this approach. © Taylor & Francis Group, LLC.